PERLINDUNGAN HUKUM TERHADAP PEMILIK RAHASIA DAGANG DI BIDANG BISNIS RESTORAN DI YOGYAKARTA DAN SURAKARTA - , Annisa Yuliana Dewi, SH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research about The Legal Protection Of Trade Secret Owner In The Restaurant Business In Yogyakarta and Surakarta, the aim of the research is to collect data of problems faced by the trade secret owner in order to get law protection. This research also analyzes the effort that can be done whether Undang-undang No. 30 year 2000 about Trade Secrets is not capable to accommodate the interests of owners of trade secrets. Research is done at Surakarta and Daerah Istimewa Yogyakarta by taking sample 4 (four) the owner of the restaurant and/or trade secret owner and 2 (two) restaurant manager. The method is done by using non-random purposive sampling method. Tool, that used in this research are interview reference and questioner. The analysis of the data result provided by literature research and field research is by using the comparative qualitative method. The result of this research shows that trade secret owner problems in getting law protection are caused by the limit of understanding and less socialization regarding to Undangundang No. 30 year 2000 about Trade Secrets and because of the limit of the trade secret owner of the economic value of their trade secrets. The effort to anticipate the need of unaccommodated trade secret owner is by HKI socialization, Trade Secrets in particular to the trade secret owner. Realization rule that control the detail of trade secrets is needed. Beside that in order to the owners of trade secrets in rural area in general, it is significant to build specific locations to accommodate HKI registration and also to provide complete information related to registration and process of HKI. Then made an agreement with the employees who work contains the command, duty, discipline, and sanctions.